Relationship of Periodontal Health and Multiple Common Stress Factors Among The Socially Deprived Women : Periodontal Health and Multiple Common Stress Factors - Malik, Aeeza; Javaid, Qurat ul Ain; Shafi, Ahmad; Khalid, Basil; Dogar, Fahad; Rehman, Rohana; Saleem, Malik (Pakistan Journal of Health Sciences, 2023)
Periodontitis is a prevalent chronic inflammatory disease in developing countries which may impose multiple negative impacts on the quality of life. The possible role of psychosocial factors in the aetiology of inflammatory periodontal diseases needs further investigations to establish the fact. Objective: To evaluate the general periodontal health and the relationship of periodontal inflammation with multiple common stress factors among the socially deprived and separated women residing in a shelter home of Multan city. Methods: This group comparative study spanned over one month. Through purposive sampling, a cohort of 115 women aged 20-40 years, residing in the SOS village shelter home, Multan for more than a month were included. Women were divided into Cases (with stress) and Controls (without stress) and were matched for age and educational status. Periodontal examination was done employing Community Periodontal Index while Life Events Scale was used to assess the type of stress. A structured and validated questionnaire was used to record the readings. Descriptive statistical measures including mean and frequency percentages along with Logistic regression analysis were used employing SPSS version 21. Results: Significant relationship (P<0.001) was found between periodontal disease and self-health-related stress, financial stress and family health-related stress. Logistic regression analysis revealed that subjects who felt self-health-related stress are 0.016, financial stress are 0.125 and family health-related stress are 0.207 times more prone to have periodontal disease than those who never or rarely felt such stresses. Conclusion: Self-health-related stress, financial stress and family health-related stress are the potential risk indicators for the development of periodontal disease among socially deprived women